Rare NOX3 Variants Confer Susceptibility to Agranulocytosis During Thyrostatic Treatment of Graves' Disease. Issue 6 (10th July 2017) - Plantinga, TS; Arts, P; Knarren, GH; Mulder, AH; Wakelkamp, IM; Hermus, AR; Joosten, LA; Netea, MG; Bisschop, PH; de Herder, WW; Beijers, HJ; de Bruin, IJ; et al.
Abstract : Agranulocytosis is a rare and serious adverse effect of antithyroid drugs, with unknown etiology. The present study aimed to uncover genetic susceptibility and underlying mechanisms of antithyroid drug‐induced agranulocytosis (ATDAC). We studied two independent families with familial Graves' disease, of which several members developed ATDAC. In addition, six sporadic ATDAC patients with Graves' disease were investigated. Whole exome sequencing analysis of affected and unaffected family members was performed to identify genetic susceptibility variants for ATDAC, followed by functional characterization of primary granulocytes from patients and unrelated healthy controls. Whole exome sequencing, cosegregation analysis, and stringent selection criteria of candidate gene variants identified NOX3 as a genetic factor related to ATDAC. Functional studies revealed increased apoptosis of methimazole‐treated granulocytes from patients carrying NOX3 variants. In conclusion, genetic variants in NOX3 may confer susceptibility to antithyroid drug‐induced apoptosis of granulocytes. These findings contribute to the understanding of the mechanisms underlying ATDAC.